Atmospheric characterization of the ultra-hot Jupiter WASP-33b: detection of Ti and V emission lines and retrieval of a broadened line profile - Cont, David; Yan, F.; Reiners, A.; Nortmann, L.; Molaverdikhani, K.; Pallé, E.; Henning, Th; Ribas, I.; Quirrenbach, Andreas; Caballero, J. A.; Amado, P. J.; Czesla, S.; et al. (Astronomy and astrophysics, 2022)
Ultra-hot Jupiters are highly irradiated gas giant exoplanets on close-in orbits around their host stars. The dayside atmospheres of these objects strongly emit thermal radiation due to their elevated temperatures, making them prime targets for characterization by emission spectroscopy. We analyzed high-resolution spectra from CARMENES, HARPS-N, and ESPaDOnS taken over eight observation nights to study the emission spectrum of WASP-33b and draw conclusions about its atmosphere. By applying the cross-correlation technique, we detected the spectral signatures of Ti i, V i, and a tentative signal of Ti ii for the first time via emission spectroscopy. These detections are an important finding because of the fundamental role of Ti- and V-bearing species in the planetary energy balance. Moreover, we assessed and confirm the presence of OH, Fe i, and Si i from previous studies. The spectral lines are all detected in emission, which unambiguously proves the presence of an inverted temperature profile in the planetary atmosphere. By performing retrievals on the emission lines of all the detected species, we determined a relatively weak atmospheric thermal inversion extending from approximately 3400 to 4000 K. We infer a supersolar metallicity close to 1.5 dex in the planetary atmosphere, and find that its emission signature undergoes significant line broadening with a Gaussian full width at half maximum of about 4.5 km s−1. Also, we find that the atmospheric temperature profile retrieved at orbital phases far from the secondary eclipse is about 300 to 700 K cooler than that measured close to the secondary eclipse, which is consistent with different day- and nightside temperatures. Moreover, retrievals performed on the emission lines of the individual chemical species lead to consistent results, which gives additional confidence to our retrieval method. Increasing the number of species included in the retrieval and expanding the set of retrieved atmospheric parameters will further advance our understanding of exoplanet atmospheres.
Gesehen am 24.04.2023